DIALOG KRITIS TRILOGI VITRUVIUS Vs. DWILOGI MANGUNWIJAYA - Burhany, Nur Rahmanina (MEKTEK, 2010)
The oldest architecture book is supposed to be the basic of West architecture theory, it is The Ten Books onArchitecture written by Marcus Polio Vitruvius was the result of his interpretation to the West architecture.It might be one of the factors supporting Mangunwijaya to make theory through his two books: FisikaBangunan and Wastu Citra, revealing the Guna and Citra as forming substances of architecture withorientation cover East and West. This critical dialog would enrich The Guna and Citra because it enlargedscope and clarified and confirmed the scope to the trilogy of Vitruvius